Hypobaric live high‐train low does not improve aerobic performance more than live low‐train low in cross‐country skiers. (22nd March 2018) - Robach, P.; Hansen, J.; Pichon, A.; Meinild Lundby, A.‐K.; Dandanell, S.; Slettaløkken Falch, G.; Hammarström, D.; Pesta, D. H.; Siebenmann, C.; Keiser, S.; Kérivel, P.; Whist, J. E.; et al.
Abstract : Live high‐train low (LHTL) using hypobaric hypoxia was previously found to improve sea‐level endurance performance in well‐trained individuals; however, confirmatory controlled data in athletes are lacking. Here, we test the hypothesis that natural‐altitude LHTL improves aerobic performance in cross‐country skiers, in conjunction with expansion of total hemoglobin mass (Hbmass, carbon monoxide rebreathing technique) promoted by accelerated erythropoiesis. Following duplicate baseline measurements at sea level over the course of 2 weeks, nineteen Norwegian cross‐country skiers (three women, sixteen men, age 20 ± 2 year, maximal oxygen uptake (VO2 max) 69 ± 5 mL/min/kg) were assigned to 26 consecutive nights spent at either low (1035 m, control, n = 8) or moderate altitude (2207 m, daily exposure 16.7 ± 0.5 hours, LHTL, n = 11). All athletes trained together daily at a common location ranging from 550 to 1500 m (21.2% of training time at 550 m, 44.2% at 550‐800 m, 16.6% at 800‐1100 m, 18.0% at 1100‐1500 m). Three test sessions at sea level were performed over the first 3 weeks after intervention. Despite the demonstration of nocturnal hypoxemia at moderate altitude (pulse oximetry), LHTL had no specific effect on serum erythropoietin, reticulocytes, Hbmass, VO2 max, or 3000‐m running performance. Also, LHTL had no specific effect on (a) running economy (VO2 assessed during steady‐state submaximal exercise), (b) respiratory capacities or efficiency of the skeletal muscle (biopsy), and (c) diffusing capacity of the lung. This study, showing similar physiological responses and performance improvements in the two groups following intervention, suggests that in young cross‐country skiers, improvements in sea‐level aerobic performance associated with LHTL may not be due to moderate‐altitude acclimatization.